Banggai Cardinalfish (Pterapogon kauderni) Potential As Bioaccumulator Of Tributyltin Contamination In The Waters Of Bitung - Bulfrit Berstian Rajagukguk; Nego E. Bataragoa; Inneke F. M. Rumengan; Wilmy E. Pelle; Suria Darwisito; Deiske A. Sumilat (Sam Ratulangi University, 2020)
At this time there have been no nekton organisms used as a bioaccumulator of the Tributyltin (TBT) pollution and mercury in tropical waters. This research aims to assess the concentration of TBT and mercury in the Pterapogon kauderni, sediment, and water in the waters of Bitung also suspect the factors that are the cause of pollution of TBT and mercury against P. Kauderni, sediment, and water in the waters of Bitung. The concentration of TBT compounds on all samples analyzed using the Gas Chromatography-Mass Spectrometer (GC-MS) tool. The results of the analysis showed that the high concentration of TBT was found in sediment (0.22 – 6.98 μg/g w.w) compared with fish ranging from 0,003-0,066 μg/g and seawater < 0.0005 μg/g (below detection of TBT limit analysis). TBT interceptions in the waters of Bitung come from a port activity and sea transportation.Keywords: Pterapogon kauderni, TributyltinAbstrakPada saat ini belum ada organisme nekton yang digunakan sebagai bioakumulator pencemaran Tributyltin (TBT) di perairan tropis. Penelitian ini bertujuan untuk menilai konsentrasi TBT pada Pterapogon kauderni, sedimen, dan air di perairan Bitung juga menduga faktor-faktor yang menjadi penyebab pencemaran TBT terhadap P. kauderni, sedimen, dan air di perairan Bitung. Konsentrasi senyawa TBT pada semua sampel dianalisis mengunakan alat Gas Chromatografy-Mass Spectrometer (GC-MS). Hasil analisis menunjukan bahwa konsentrasi TBT paling tinggi terdapat pada sedimen (0,22 – 6,98 µg/g w.w) dibandingkan dengan ikan yang berkisar 0,003-0,066 µg/g dan air laut <0,0005 µg/g (dibawah deteksi limit analisis TBT). Pencemaran TBT yang terdapat di perairan Bitung berasal dari aktivitas pelabuhan dan transportasi laut.Kata kunci: Pterapogon kauderni, Tributyltin.